Transnational social mobility of minorities: A comparative analysis of 14 immigrant minority groups - Elyakim Kislev (IZA Journal of Development and Migration, 2018)
There is extensive scholarship on the condition of being a minority in one's home country and vast literature on the experience of immigrants in host countries. However, almost no attention has been paid to the distinct mechanisms pertaining to immigrants who were minorities in the source country and moved to another. This paper integrates the literature on minorities with that of migration and addresses this gap by developing a theory of a growing phenomenon: the transnational social mobility of minorities. Using the US census and the American Community Survey, 14 groups of minorities (e.g., British Pakistanis) who immigrated to the USA are compared to the corresponding majority groups from the same country (e.g., the British majority). Findings show that all minorities have a lower starting point than the corresponding majority group from the same country. However, non-black minorities succeed faster and, in some cases, even pass majorities over time. In contrast, black immigrant minorities remain disadvantaged in comparison to whites from the same country.
Keywords: J15; J61; 330; Migration; Minorities; Labor markets; Race; Ethnicity; USA